Al-Iqtishad : Jurnal Ilmu Ekonomi Syariah ( Journal of Islamic Economics) - Teguh Budiman (Fakultas Syariah dan Hukum UIN Syahida Jakarta, 2017)
Islamic Bank Listed In Financial Market: Risk, Governance, Earning, And Capital Teguh Budiman1 , Farida Titik Kristanti2 , Wardhana3 1-12 Building An Early Warning Towards The Resilience Of Islamic Banking In Indonesia Dimas Bagus Wiranatakusuma1 , Jarita Duasa 13-32 Asset Liability Management Of Conventional And Islamic Banks In Malaysia Yee Loon Mun1 , Hassanudin Mohd Thas Thaker2 33-52 The Indonesian Islamic Bank’s Spin-Off: A Study In Regional Development Banks Ismawati Haribowo 53-68 Determinants Of The Islamic Social Reporting Disclosure Uun Sunarsih1 , Ferdiyansyah2 69-80 Strategic Approach For Optimizing Of Zakah Institution Performance: Customer Relationship Management Estu Widarwati1 , Nur Choirul Afif2 , Muhamad Zazim3 81-94 Greece Financial Crises And Sukuk Markets: Experience From Gulf Countries Aldrin Herwany1 , Erie Febrian2 , Imam Buchari3 95-106 Tawhidic Based Economic System: A Preliminary Conception Nurul Hilmiyah1 , Bayu Taufiq Possumah2 , Muhammad Hakimi Mohd. Shafiai3 107-124 Consumers Demand On Halal Cosmetics And Personal Care Products In Indonesian Muniaty Aisyah 125-142 A Comparative Study On Poverty Alleviation Between Moslem And Non-Moslem Populated Countrie Ahmad Hudaifah1 , Shochrul Rohmatul Ajija 143-164